Tracked Changes. ISO general purpose metric screw threads. Tolerances. Limits of sizes for hot-dip galvanized external screw threads to mate with internal screw threads tapped with tolerance position H or G after galvanizing Part 4, (30th July 2021) - British Standards Institution,
No abstract available